Efficacy of a novel orally active SERD AZD9496 against hormone dependent post-menopausal breast cancer depends on inhibition of cellular aromatase activity. Issue 202 (September 2020) - Kazi, Armina; Goloubeva, Olga; Schech, Amanda; Yu, Stephen; Sabnis, Gauri J
Abstract: Treatment of hormone sensitive breast cancer tumors with endocrine therapy such as antiestrogens or aromatase inhibitors has improved the outcome significantly. Studies including our own have shown that downregulation of ERα with pure antiestrogen fulvestrant in combination with aromatase inhibitors may prolong responsiveness of the tumors to endocrine therapy. Fulvestrant has been studied as second line or first line treatment for post-menopausal hormone receptor positive breast cancers as a single agent or in combination with AIs. Studies have also suggested that further escalation of dose may improve benefit. However, dose escalation of fulvestrant, which is administered via intramuscular injection, is difficult due to its poor solubility. To overcome this shortcoming of an injectable drug, a novel orally active antiestrogen, AZD9496 was developed. In addition to being orally active, AZD9496 is designed as a selective ERα downregulator (SERD). In the current study, we compared the effect of AZD9496 and fulvestrant on the growth of MCF-7Ca (human estrogen receptor positive MCF-7 cells stably transfected with human placental aromatase gene) xenografts grown in ovariectomized athymic nude mice. AZD9496 was also compared to fulvestrant in vitro as a single agent or in combination with anastrozole. Our current study shows that AZD9496 is equally effective as fulvestrant at controlling the growth of hormone sensitive human breast cancer tumors. Similar to fulvestrant, AZD9496 inhibits cellular aromatase activity through ERα mediated signaling. However, unlike fulvestrant, combination of AZD9496 with anastrozole did not produce increased tumor inhibition. Our results show that AZD9496 was significantly better at inhibiting cellular aromatase which contributed to its anticancer activity. Next, we measured the effect of AZD9496 on the mouse uterus. Uterine weight of mice treated with AZD9496 was significantly lower than that for mice treated with androstenedione. This reduction in uterine weight was due to AZD9496 mediated inhibition of aromatase activity and not a direct effect on uterine ERα expression. We also observed that anti-cancer efficacy of AZD9496 depended on its ability to inhibit cellular aromatase. These results suggest that AZD9496 may be a better alternative to fulvestrant due to its selectivity for mammary ER and ability to inhibit aromatase in addition of downregulating ERα that can be obtained upon oral administration. As such, AZD9496 may prove to be a better option than fulvestrant for the treatment of hormone sensitive human breast cancer.